2019
DOI: 10.1007/s10311-019-00883-z
|View full text |Cite
|
Sign up to set email alerts
|

The proton binding properties of biosorbents

Abstract: A broad variety of materials of biological origin have been successfully used in 27 recent decades for the removal of pollutants from solution. These biosorbents 28 present a range of natural polymers that play a key role on their adsorption capacity. It is therefore critical to understand the physicochemical properties of the chemical groups that form these polymers. The acid-base properties of 31 biomass are affected by pH, ionic strength and medium composition. 32Nevertheless, these crucial parameters are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…Potentiometric titrations using glass/selective electrodes are routinely applied for the physicochemical analysis of e.g. biomass (Lodeiro et al, 2019) and fulvic and humic substances of terrestrial or freshwater origin (David et al, 2010;Koopal et al, 2005). In coastal waters like the Baltic Sea, a significant part of the DOM pool is of terrestrial origin and supplied by rivers (Deutsch et al, 2012;Hoikkala et al, 2015;Seidel et al, 2017), although overall a very small fraction of terrestrial DOM (b0.03%) is exported to the ocean (Cai et al, 1998;Carlson and Hansell, 2015;Dittmar and Stubbins, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Potentiometric titrations using glass/selective electrodes are routinely applied for the physicochemical analysis of e.g. biomass (Lodeiro et al, 2019) and fulvic and humic substances of terrestrial or freshwater origin (David et al, 2010;Koopal et al, 2005). In coastal waters like the Baltic Sea, a significant part of the DOM pool is of terrestrial origin and supplied by rivers (Deutsch et al, 2012;Hoikkala et al, 2015;Seidel et al, 2017), although overall a very small fraction of terrestrial DOM (b0.03%) is exported to the ocean (Cai et al, 1998;Carlson and Hansell, 2015;Dittmar and Stubbins, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The total amount of proton binding groups in the North Atlantic SPE–DOM ( Q maxH,tot ) was not significantly different between the surface (112.7 ± 5.8 mmol·mol C –1 ) and deep (117.3 ± 5.6 mmol·mol C –1 ) samples. The total proton binding represents a maximum of binding sites for chemical species that can compete with protons for the DOM binding sites, with a predominantly covalent behavior, 40 e.g., most trace metals in seawater. On average, 11.4 ± 0.6% of the C atoms in our extracted North Atlantic DOM therefore have a functional group with a binding site for ionic species.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the mechanism of ion exchange exerts a fundamental control, at least for the retention of specific metals. In this context, the elevated proton binding capacity of Sargassum muticum (2.40-2.61 mol/kg of alga) anticipates success of micro-macronutrient amendments using this alga or its residues [69]. For example, S. muticum collected from the same geographical area as the specimens used for the present study showed adsorption capacities ranging between 1.12-1.42 mmol metal/g seaweed [23].…”
Section: Mineral Amendmentmentioning
confidence: 99%